Monitoring and Surveillance of Forest Insects - Brockerhoff, Eckehard G. (2023)
Monitoring of insect populations is widely used in forest entomology in the context of biodiversity studies, as an aspect of pest management, and for the detection and surveillance of non-native invasive species. In particular, monitoring is undertaken to obtain information on the presence or abundance of particular species, to study their phenology (e.g. the time of oviposition or flight periods), to predict pest population size, spread and damage, or to determine if pest management activities are required. A wide variety of methods are being used for these purposes including physical surveys, the use of insect traps, molecular methods, as well as aerial surveys and remote sensing. This chapter focusses on some of the more important methods to provide an overview of the objectives and applications of monitoring and surveillance of forest insects. The principles of each method and common uses are explained and illustrated with case studies on prominent forest insects including the pine processionary moth (Thaumetopoea pityocampa), the Sirex wood wasp (Sirex noctilio), spongy moth (Lymantria dispar), bark beetles such as Ips typographus, and the brown spruce longhorn beetle (Tetropium fuscum). The chapter also explores statistical considerations and issues such as imperfect relationships between trap catch and the local population size of target species. Niche methods that are not widely used but have strengths in some situations (e.g. detector dogs for detection of Anoplophora glabripennis and other invasive species) or are still in development (e.g. e-noses and acoustic detection) are also discussed.